Transcriptional and proteomic responses to carbon starvation in Paracoccidioides. - Patrícia de Sousa Lima; Luciana Casaletti; Alexandre Melo Bailão; Ana Tereza Ribeiro de Vasconcelos; Gabriel da Rocha Fernandes; Célia Maria de Almeida Soares (Public Library of Science (PLoS), 2014)
BACKGROUND: The genus Paracoccidioides comprises human thermal dimorphic fungi, which cause paracoccidioidomycosis (PCM), an important mycosis in Latin America. Adaptation to environmental conditions is key to fungal survival during human host infection. The adaptability of carbon metabolism is a vital fitness attribute during pathogenesis. METHODOLOGY/PRINCIPAL FINDINGS: The fungal pathogen Paracoccidioides spp. is exposed to numerous adverse conditions, such as nutrient deprivation, in the human host. In this study, a comprehensive response of Paracoccidioides, Pb01, under carbon starvation was investigated using high-resolution transcriptomic (RNAseq) and proteomic (NanoUPLC-MSE) approaches. A total of 1,063 transcripts and 421 proteins were differentially regulated, providing a global view of metabolic reprogramming during carbon starvation. The main changes were those related to cells shifting to gluconeogenesis and ethanol production, supported by the degradation of amino acids and fatty acids and by the modulation of the glyoxylate and tricarboxylic cycles. This proposed carbon flow hypothesis was supported by gene and protein expression profiles assessed using qRT-PCR and western blot analysis, respectively, as well as using enzymatic, cell dry weight and fungus-macrophage interaction assays. The carbon source provides a survival advantage to Paracoccidioides inside macrophages. CONCLUSIONS/SIGNIFICANCE: For a complete understanding of the physiological processes in an organism, the integration of approaches addressing different levels of regulation is important. To the best of our knowledge, this report presents the first description of the responses of Paracoccidioides spp. to host-like conditions using large-scale expression approaches. The alternative metabolic pathways that could be adopted by the organism during carbon starvation can be important for a better understanding of the fungal adaptation to the host, because systems for detecting and responding to carbon sources play a major role in adaptation and persistence in the host niche.